Equestrian Sports In The Surkhandarya Oasis: History, Current State, And Development Strategy (Eurasian Journal of History, Geography and Economics, 2024)
This article is dedicated to the development trends of equestrian sports in the Surkhan Oasis. The study is based on the region's rich historical and cultural heritage, examining the processes of formation and development of equestrian sports. The article analyzes the establishment of the first equestrian clubs in the oasis, their activities, modern development trends, and socio-economic significance. It also explores the role of equestrian sports in promoting tourism in the region and fostering a healthy lifestyle among youth. The article addresses current challenges hindering the industry's development and proposes solutions to overcome them.